PENGELOLAAN KELAS DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SD IT ANNABA CIASEM - Muhammad Noer Aksel Farizal; Acep Nurlaeli (STAI Ihyaul Ulum Gresik, 2026)
Classroom management should be carried out with procedures that have been used as a reference source for each study, with good and conceptual class management will make an effective and efficient classroom management for an educator. As educators, teachers are required to be able to apply various methods for classroom management, both approach techniques, disciplinary coaching and managing obstacles and solutions in dealing with classroom management. This is all aimed at good and effective classroom management. Various approaches were applied to achieve a result that was in line with the researchers' expectations for more efficient classroom management at SD IT Annaba Ciasem.